Identification of food additive types in ultra-processed food products sold at the canteen of SD Negeri 59 Kendari - Paridah Paridah; Agnes Mersatika Hartoyo (PT WIM Solusi Prima, 2026)
The consumption of ultra-processed foods (UPF) among school-aged children is rising and raising concerns, as these products typically contain various food additives used to enhance flavor, texture, aroma, and shelf life. Specifically in Kendari City, there is insufficient information regarding the types of UPF and food additives circulating in school environments. This study aimed to identify the types of food additives found in UPF products sold at the canteen of SD Negeri 59 Kendari. This descriptive observational study was conducted in May 2026 at the SD Negeri 59 Kendari canteen. All packaged food products sold in the school canteen were included in the sample using a total sampling method. UPF categories were identified using the NOVA classification system, while food additives were identified based on information found on packaging labels, in accordance with the regulations of the National Agency of Drug and Food Control (BPOM). Data were analyzed descriptively and presented as frequency distributions and percentages. A total of 62 packaged food products were identified, all of which fell into the UPF category. Snacks were the most common product type (29.0%), followed by biscuits (19.4%), candies (14.5%), wafers (12.9%), and instant noodles (9.7%). Sweeteners were the most frequently used class of food additives (22.9%). Monosodium glutamate (MSG/E621) was the most types of food additives. Most products contained 2–3 classes of food additives. The study concludes that a variety of classes and types of food additives are used in the UPF products sold at the SD Negeri 59 Kendari canteen. These findings can serve as a basis for food label literacy education, the establishment of healthy canteens, and the strengthening of policies to provide healthier food options in schools.